Surface functional carbon dots: chemical engineering applications beyond optical properties. Issue 46 (6th November 2020) - Xu, Xiaokai; Li, Yadong; Hu, Guangqi; Mo, Luoqi; Zheng, Mingtao; Lei, Bingfu; Zhang, Xuejie; Hu, Chaofan; Zhuang, Jianle; Liu, Yingliang
Abstract : The surface function of carbon dots mainly includes three aspects: CDs used as structural regulators, chemical additives, reinforcing reagents to improve water dispersibility and enhance mechanical properties of materials. Abstract : As emerging carbon materials, carbon dots (CDs) have received extensive attention in recent years. Since CDs have excellent optical properties, most reports on carbon dots focus on research of their optical applications. However, their diverse surface functional groups also afford broad application prospects in chemical engineering. This review article focuses on the research progress in the chemical applications of CDs in the following three aspects: CDs used as structural regulators of the morphology and size of materials; CDs used as chemical additives, such as consolidant, antirust, antifreeze, lubricant, and scale inhibitors; CDs used as reinforcing reagents to improve water dispersibility and enhance mechanical properties of materials. Finally, we focus on existing problems in this field and look forward in the direction of future development.